1998
DOI: 10.1109/52.714843
|View full text |Cite
|
Sign up to set email alerts
|

Interrupts: just a minute never is

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 3 publications
4
80
0
Order By: Relevance
“…The results show that, similarly to Solingen et al (1998) the negative aspects are more prominent than that of any positive interrupt effects on employees. During the study, there were signs that the interrupt disturbed concentration where a recovery time existed, and it caused task delay where additional handling time was present.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…The results show that, similarly to Solingen et al (1998) the negative aspects are more prominent than that of any positive interrupt effects on employees. During the study, there were signs that the interrupt disturbed concentration where a recovery time existed, and it caused task delay where additional handling time was present.…”
Section: Resultsmentioning
confidence: 53%
“…Similarly to Solingen et al (1998) they compared email to another medium of interrupt, the telephone. Solingen et al (1998) claim that interruptions have three phases: occurrence, handling and recovery.…”
Section: The Known Effects Of Task Interruption and Email Addictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have investigated work practices and work fragmentation in detail from various perspectives, specifically the effect of interruptions on fragmentation (e.g., [6], [7], [8], [9]) and how developers organize their work in terms of tasks and working spheres (e.g., [5], [10]). Using both a diary and an observational study format to understand software developer work practices, Perry and colleagues gained several insights, including that most time was spent coding, and that there was a substantial amount of unplanned interaction with colleagues [2].…”
Section: Introductionmentioning
confidence: 99%
“…Interruptions in software development: Van Solingen et al [20] found that every time a software developer is interrupted by others (e.g., individuals from other or own project team), it costs on average fifteen minutes to get back to focus on the task he/she was performing. Parnin and DeLine [21] found that besides the initial delay, the quality of code produced following an interruption is lower, which corresponds to the residual impact found by psychology studies.…”
Section: Software Development: Interruptions and Multiple Projectsmentioning
confidence: 99%